Tumor necrosis factor alpha neutralization has no direct effect on parasite burden, but causes impaired IFN-γ production by spleen cells from human visceral leishmaniasis patients. (September 2016) - Singh, Neetu; Kumar, Rajiv; Engwerda, Christian; Sacks, David; Nylen, Susanne; Sundar, Shyam
Highlights: Leishmania antigen specific TNF-α is actively produced in spleen cell cultures. TNF-α neutralization has no effect on Leishmania parasite replication in spleen. TNF-α blockade significantly reduces IFN-γ production in spleen cell cultures. TNF-α and it's receptors' expression is not altered in pre-post splenic tissues. TNF-α has no impact on antigen specific IL-10, IFN-γ production in whole blood. Abstract: The pro-inflammatory cytokine tumor necrosis factor (TNF)-α has an important role in control of experimental Leishmania donovani infection. Less is known about the role of TNF-α in human visceral leishmaniasis (VL). Evidence for a protective role is primarily based on case reports of VL development in individuals treated with TNF-α neutralizing antibody. In this study, we have evaluated how TNF-α neutralization affects parasite replication and cytokine production in ex vivo splenic aspirates (SA) from active VL patients. The effect of TNF-α neutralization on cell mediated antigen specific responses were also evaluated using whole blood cultures. Neutralization of TNF-α did not affect parasite numbers in SA cultures. Interferon (IFN)-γ levels were significantly reduced, but interleukin (IL)-10 levels were unchanged in these cultures. Leishmania antigen stimulated SA produced significant TNF-α which suggests that TNF-α is actively produced in VL spleen. Further it stimulates IFN-γ production, but no direct effect on parasite replication.